G71(P) Promoting normal admission temperature for neonates. (May 2019) - Patel, R; Barnett, M; Mainie, P
Abstract : Aim: Hypothermia contributes to increased morbidity and mortality rates in neonates of all birth weights and ages, but early recognition can improve prognosis. A 2018 RCPCH National Neonatal Audit Programme measure looks at the proportion of babies less than 32 weeks gestational age with a normal first temperature within an hour of birth. We analysed the number of neonates, of all gestational ages, with normal admission temperatures and whether completing a 'temperature admission proforma' at the time of delivery affected these numbers. Methods: Patients for inclusion were identified from the BadgerNet database, between 1 st March 2018 to 1 st June 2018. Staff were requested to complete a temperature admission audit proforma at the time of birth, detailing management at birth promoting normothermia. Three proformas were used depending on gestational age (<31 weeks, 31–36+6 weeks, >37 weeks). Proformas not completed at the time of delivery, were retrospectively completed by the admitting team. The admission temperatures were taken from BadgerNet. Results: The NNAP standards are that the temperature should be taken within an hour of birth for 98% of babies, and normothermia should be achieved in 90% of babies. 100% of neonates (n=73) had a temperature measured within one hour of birth. If a temperature admission proforma was completed at the time of delivery (n=48), 81% of neonates were normothermic on admission. If a proforma was completed retrospectively (n=25), only 36% were normothermic on admission. Conclusion: We achieved the NNAP standard of measuring admission temperatures in over 98% of neonates within one hour of birth. However, if the temperature admission proformas were not completed at the time of birth, we were less likely to achieve a normothermic admission temperature. Using feedback on the layout of the proformas, we introduced new, updated proformas, including more measures to encourage normothermia and also external factors, such as suspected sepsis, which may influence the admission temperature. We gave two teaching sessions on promoting normothermia and encouraged staff to review the new proforma prior to attendance at deliveries expected to require admission, anticipating these measures will improve the number of neonates with normothermic admission temperatures.